Composition in fatty acids of mature milk of nursing mothers - Ronilson Ferreira Freitas; Mariana de Souza Macedo; Angelina do Carmo Lessa; Vany Perpétua Ferraz; Nayanne Oliveira Soares; Brenda Evellyn Veríssimo Martins; Nísia Andrade Villela Dessimoni Pinto; Romero Alves Teixeira
Abstract Objectives: to determine the fatty acid composition of mature milk of nursing mothers and its distribution according to some maternal variables. Methods: this is a cross-sectional observational epidemiological study based on the eva-luation of the fatty acid profile of mature human milk. Samples of mature breast milk were taken from 106 nursing mothers, by manual milking and who were after the 5th postpartum week. The milk fat extraction was carried out by using the Bligh and Dyer method and methy-lated with 0.25 mol/L sodium methoxide in methanol diethyl ether. The fatty acid of the milk profile was determined by a Gas Chromatograph equipped with a flame ionization detector. Results: among the saturated fatty acids, the highest values were observed for palmitic (C16:0), stearic (C18:0), myristic (C14:0) and lauric (C12:0) fatty acids, respectively. Among the monounsaturated fatty acids, there was a higher contribution of oleic (C18:1) and palmi-toleic (C16:1) fatty acids, respectively. The total essential fatty acids (linoleic and α-linolenic) was 14.94%. Conclusions: a low content of essential fatty acids in the breast milk of the nursing mothers was observed in the present study, which are important for infant growth and deve-lopment. We suggest the need to implement nutrition education strategies aimed for pregnant women and nursing mothers who should be advised to eat healthier foods.